Measurement of ω meson production in pp collisions at s $$ \sqrt{s} $$ = 13 TeV - The ALICE collaboration; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Journal of High Energy Physics)
Abstract The p T-differential cross section of ω meson production in pp collisions at s $$ \sqrt{s} $$ = 13 TeV at midrapidity (|y| < 0.5) was measured with the ALICE detector at the LHC, covering an unprecedented transverse-momentum range of 1.6 < p T < 50 GeV/c. The meson is reconstructed via the ω → π + π − π 0 decay channel. The results are compared with various theoretical calculations: PYTHIA8.2 with the Monash 2013 tune overestimates the data by up to 50%, whereas good agreement is observed with Next-to-Leading Order (NLO) calculations incorporating ω fragmentation using a broken SU(3) model. The ω/π 0 ratio is presented and compared with theoretical calculations and the available measurements at lower collision energies. The presented data triples the p T ranges of previously available measurements. A constant ratio of C ω/π0 = 0.578 ± 0.006 (stat.) ± 0.013 (syst.) is found above a transverse momentum of 4 GeV/c, which is in agreement with previous findings at lower collision energies within the systematic and statistical uncertainties.